Big data and urban form: a systematic review - Vladan Djokić; Aleksandra Djordjević; Aleksandra Milovanović (Journal of Big Data)
Abstract The study of urban form as a central interest of architects, planners, and urban designers has faced various challenges over time, affecting the representation of this topic in the research, educational, and practical arenas. Recently, with the actualization of big data, the study of urban form is going under change as well, where these technological advancements present both the great potential for urban form analysis, understanding, modelling, simulation, and even imagination, and a challenge for the profession of architecture and urbanism itself, which must come to grips with the growing field of big data research. This paper delves into the significance of urban form as a composition of the ground plan (streets, blocks, plots, and buildings), building fabric, land and building utilization, and social structure, explicitly emphasizing unfolding the complexities concerning big data. The central method used in the research is the systematic literature review applied to investigate the interrelation between urban form and big data. The research follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol by systematizing recent research from the Web of Science (WOS) database. The paper aims to structure knowledge into a coherent framework, reveal relationships and patterns, create a valuable classification for future research, and identify gaps within the research field. The main results should contribute to painting the overall picture of the research landscape on big data and urban form.